ANALISIS PENERAPAN AKUNTANSI ZAKAT , INFAQ, SHODAQOH PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) PROVINSI JAWA BARAT - Mishelei Loen, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The potential of zakat in Indonesia is currently around Rp 217 Trillion. Four times from the Ministry of Religion budget. Very big. However, one of the fundamental problems is the awareness of muzakki to fulfill zakat through zakat institutions is very small. The zakat institution in Indonesia is called the National Zakat Amil Agency (BAZNAS). The West Java Provincial Amil Zakat Agency has the main task of collecting, managing, distributing and empowering zakat, infaq, shadaqah funds, from all Muslims in West Java Province, based on the Zakat Act No.23 of the fifth part of article 29 paragraph 1 every year make annual reports as accountability. The accountability referred to in this case is the making of financial statements that are in accordance with the terms and conditions set out in the financial accounting standard PSAK 109 and are inseparable from sharia principles. The purpose of this study was to find out and apply PSAK109 regarding accounting for zakat infaq and almsgiving at the National Zakat Amil Agency (BAZNAS) of West Java Province. The method of analyzing the research conducted is descriptive qualitative analysis method. The results of this study indicate that the BAZNAS of West Java Province is in accordance with PSAK 109. However, the recognition of the burden of collection and distribution of zakat is not in accordance with PSAK 109